Heat exposure and pediatric immune thrombocytopenia in Japan from 2011 to 2022: a nationwide space-time-stratified case-crossover study - Nobutoshi Nawa; Hisaaki Nishimura; Kiyohide Fushimi; Takeo Fujiwara (Haematologica)
Not available.